A video analysis primer for swim coaches - Boder, R. H. (2010)
Here are the steps the author tooks to incorporate video analysis into his YMCA competitive swimming programs in 2006. It explains briefly: - Equipment needed for video analysis, - Organizational details and "best practices" of clinics and camps he has participated in, - Results of his programs and - Thoughts and tips he learned from other coaches and the hard way.